Dehydrative condensation of carbonyls with non-acidic methylenes enabled by light: synthesis of benzofurans. Issue 89 (20th October 2016) - Liu, Wenbo; Chen, Ning; Yang, Xiaobo; Li, Lu; Li, Chao-Jun
Abstract : Condensation of carbonyls with non-acidic methylenes such as those adjacent to heteroatoms and allylic types to generate CC bonds is challenging but highly desirable. Abstract : Condensation of carbonyls with non-acidic methylenes such as those adjacent to heteroatoms and allylic types to generate CC bonds is challenging but highly desirable. Inventing novel methods that can accomplish such condensations can enrich synthetic chemists' toolbox. Herein, we report a simple, clean, and high yielding protocol promoted by light to achieve condensation of non-acidic methylenes with carbonyls. As examples to demonstrate the power of this methodology, one class of ubiquitous and highly important heterocycles, i.e. benzofurans, were synthesized with broad functional group compatibility. Furthermore, intermolecular condensations were also briefly investigated.